Space shuttle dropped down the trapped proton doses at international space station - Dachev, Tsvetan; Semkova, Jordanka (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The data from three Bulgarian build instruments on the International Space Station (ISS): Liuin-5 inside PIERS module of Russian segment, R3DE instrument outside at the European Technological Expose Facility (EuTEF) on the ESA Columbus module and R3DR instrument outside Russian “Zvezda” module shows that the docking of the Space Shuttle with the ISS decreased the trapped proton maximal doses in the region of the South-Atlantic Anomaly (SAA) by factor of 1.25 to 2 in dependence from the local shielding and the distance to the Space Shuttle. The analysis of the ascending/descending SAA dose rate maximums of the instruments shows that the effect can be simply explained by the additional shielding against the 30 to 150 MeV protons of the inner radiation belt in the region of the SAA, provided by the 78 tons Shuttle to the instruments and by changing of the ISS 3D mass distribution when the ISS rotates.